Interactions between Sheets of Phonons in Liquid 4He - Vovk, R.V.; Williams, C.D.H.; Wyatt, A.F.G. (My University, 2003)
We have created two sheets of 1 K phonons in liquid 4He at 55 mK such that they intersect each other as they move towards a common point. If the two sheets have a small angle between them, they interact strongly and create a hot line in the liquid helium. This line is continuously fed with energy from the two sheets and loses energy by creating high-energy phonons. If the angle between the sheets is larger than 30 they do not interact but pass through each other. These results give direct evidence for the composition of the sheets: they comprise strongly interacting low-energy phonons which occupy a narrow cone in momentum space.
Keywords: low-energy phonons; liquid 4He; phonon pulses